Profiling the 'deamidome' of complex biosamples using mixed-mode chromatography-coupled tandem mass spectrometry - Sze, Siu Kwan (2022)
Deamidation is a spontaneous degenerative protein modification (DPM) that disrupts the structure and function of both endogenous proteins and various therapeutic agents. While deamidation has long been recognized as a critical event in human aging and multiple degenerative diseases, research progress in this field has been restricted by the technical challenges associated with studying this DPM in complex biological samples. Asparagine (Asn) deamidation generates L-aspartic acid (L-Asp), D-aspartic acid (D-Asp), L-isoaspartic acid (L-isoAsp) or D-isoaspartic acid (D-isoAsp) residues at the same position of Asn in the affected protein, but each of these amino acids displays similar hydrophobicity and cannot be effectively separated by reverse phase liquid chromatography. The Asp and isoAsp isoforms are also difficult to resolve using mass spectrometry since they have the same mass and fragmentation pattern in MS/MS. Moreover, the 13C peaks of the amidated peptide are often misassigned as monoisotopic peaks of the corresponding deamidated peptides in protein database searches. Furthermore, typical protein isolation and proteomic sample preparation methods induce artificial deamidation that cannot be distinguished from the physiological forms. To better understand the role of deamidation in biological aging and degenerative pathologies, new technologies are now being developed to address these analytical challenges, including mixed mode electrostatic-interaction modified hydrophilic interaction liquid chromatography (emHILIC). When coupled to high resolution, high accuracy tandem mass spectrometry this technology enables unprecedented, proteome-wide study of the 'deamidome' of complex samples. The current article therefore reviews recent advances in sample preparation methods, emHILIC-MS/MS technology, and MS instrumentation / data processing approaches to achieving accurate and reliable characterization of protein deamidation in complex biological and clinical samples.